Physical and chemical properties of some hazelnut varieties grown in Portugal - Ferrão, Ana Cristina (2021)
Worldwide there has been an increase in the demand for dried fruits. In Portugal, hazelnut is the dry fruit with the less cultivated area, however the country has conditions for a good production. This work intended to analyse the physical and chemical properties of seven hazelnut varieties grown in Portugal, named Negreta, Gunslebert, Tonda de Giffoni, Grada de Viseu, Butler, Segorbe and Longa de Espanha. For that purpose, hazelnut fruits were evaluated for biometric characteristics, apparent and true densities, colour, texture, nutritional parameters (moisture, ash, lipids content, protein, fibre and water activity), oxidative stability index and specific extinction coefficients (K232, K264, K268 and K272). The results showed that, in general, there were statistically significant differences among the varieties under study. Hazelnuts of variety Longa de Espanha revealed to be more elongated and the variety Butler had heavier fruits, both in shell and kernel. The variety Grada de Viseu was harder in the shell being the kernels of variety Segorbe softer but more resistant to fracture. For all varieties, fat was the major chemical component. The lowest extinction coefficient, K232, was found for Negreta, indicating that this variety presented a lower degree of primary oxidation products. The other specific extinction coefficients were relatively low for all samples. Moreover, Tonda de Giffoni was the variety with the higher oxidation stability. This work highlighted the differences in hazelnuts according to the variety, confirming the importance to perform more studies in this area since these results can be very useful in the hazelnut sector.